MACROPHAGES DISPLAY PRO-INFLAMMATORY PHENOTYPES IN EUTOPIC ENDOMETRIUM OF WOMEN WITH ENDOMETRIOSIS WITH RELEVANCE TO AN INFECTIOUS ETIOLOGY OF THE DISEASE - Vallvé-Juanico, Júlia (Fertil Steril, 2019)
OBJECTIVE: To phenotype transcriptomically macrophages M1 (Mφ1) and M2 (Mφ2) in the endometrium of women with endometriosis. DESIGN: Prospective experimental study. SETTING: University research laboratory. PATIENT(S): Six women with endometriosis and five controls without disease, in the secretory phase of the menstrual cycle. INTERVENTION(S): Mφ1, Mφ2, uterine natural killer (uNK) and regulatory-T (Treg) cells were isolated from human endometrium using a uniquely designed cell-specific fluorescence activating cell sorting panel. Transcriptome profiles were assessed by RNA-high sequencing, bioinformatic and biological pathway analyses. MAIN OUTCOMES MEASURE(S): Differential gene expression between Mφ1 and Mφ2 in women with and without endometriosis, and in Mφ1 versus Mφ2 in each group, were determined and involved different bioloigcal and signaling pathways. RESULT(S): Flow cytometry analysis showed no significant differences in total numbers of leukocytes between control and endometriosis groups, although Mφ1 were higher in endometriosis versus controls. Statistical transcriptomic analysis was performed only in Mφ1 and Mφ2 populations due to larger sample sizes. Bioinformatic analyses revealed that in women with endometriosis endometrial Mφ1 are more pro-inflammatory than controls and Mφ2 paradoxically have a pro-inflammatory phenotype. CONCLUSION(S): As Mφ are phenotypically plastic and their polarization state depends on their microenvironment, the altered endometrial environment in women with endometriosis may promote endometrial Mφ2 polarization and an Mφ1 pro-inflammatory phenotype. Moreover, aberrant phenotypes of Mφ may contribute to abnormal gene expression of eutopic endometrium and a pro-inflammatory environment in women with endometriosis relevant to the pathophysiology of the disease and compromised reproductive outcomes.